Characteristics of VOC Composition at Urban and Suburban Sites of New Delhi, India in Winter. Issue 12 (14th June 2022) - Tripathi, Nidhi; Sahu, L. K.; Wang, Liwei; Vats, Pawan; Soni, Meghna; Kumar, Purushottam; Satish, R. V.; Bhattu, Deepika; Sahu, Ravi; Patel, Kashyap; Rai, Pragati; Kumar, Varun; et al.
Abstract: Simultaneous measurements of volatile organic compounds (VOCs) using two PTR‐TOF‐MS instruments were conducted at urban and suburban sites of New Delhi during the winter of 2018. The time series of VOC mixing ratios show substantial variations mainly influenced by local emissions and meteorological conditions. Mixing ratios of methanol (∼28 ppbv), acetaldehyde (7.7 ppbv), acetone (10.6 ppbv), isoprene (2.8 ppbv) and monoterpenes (0.84 ppbv) at the suburban site were higher than those at the urban site, while levels of aromatic VOCs were almost similar. The strong nighttime correlations of isoprene and monoterpenes with CO and benzene at the urban site indicate their predominant anthropogenic origin. Higher emission ratios of ∆VOCs/∆CO and ∆VOCs/∆benzene than those reported for vehicular exhaust suggest the contributions of other sources. In addition to vehicular emissions, episodes of biomass burning, industrial plumes and aged air strongly influenced the levels of VOCs at the suburban site. Despite the predominant primary anthropogenic emissions, the higher daytime enhancements of OVOCs/CO ratios indicate additional contributions of OVOCs from secondary/biogenic sources. The secondary formation of OVOCs in moderately aged air masses was noticeable at the suburban site. Using the source‐tracer‐ratio method, the estimated biogenic contributions of isoprene (71%) and acetone (65%) during daytime at the suburban site were significantly higher than those for the urban site. The photochemical box model simulations suggest that daytime ozone formation was under the VOC‐limited regime. The present study highlights the impact of different emission sources, photochemical processes and meteorological conditions on the composition and concentration of VOCs in the Delhi region. Plain Language Summary: Contributions of natural and anthropogenic sources of volatile organic compounds (VOCs) vary on local and regional scales. In recent years, emission from the use of fossil fuels is the main anthropogenic source of ambient air VOCs in the urban regions of developing countries. Other sources such as biomass/biofuel burning and biogenic emissions also influence urban air quality in tropical regions. The distinction between biogenic and anthropogenic contributions of VOCs in urban air is not straightforward because many VOCs are emitted from several co‐located sources. In this study, we performed simultaneous VOC measurements using state‐of‐art instruments at the urban and suburban sites of New Delhi in the polluted Indo‐Gangetic Plains of India during the winter season. Besides the impact of primary sources, we have also investigated the roles of photochemical secondary formation of oxygenated VOCs. Our findings will help policymakers develop strategies for controlling primary and secondary pollutants in this tropical urban region. Key Points: Vehicular exhaust, episodes of biomass burning, industrial plumes and aged air strongly influenced the concentration and composition of VOCs Higher enhancements of OVOCs in photochemically aged air masses reveal their significant secondary productions at the suburban site The estimated biogenic contributions to ambient air isoprene for the suburban site were higher than those for the urban site